Tales from the yoga studio a novel - Mitchell, Rain (Plume, 2011)
Lee struggles to decide whether to stay at her mom-and-pop yoga studio in Los Angeles, where she and four of her clients have forged strong friendships, or take a dream job with a large yoga-studio chain.